Allocation and sizing of distributed generation (DG) using Particle Swarm Optimization (PSO) technique for loss minimization: article / Junainah Pardi - Pardi, Junainah (2009)
Distributed generator (DG) is playing major role to supply energy resources and also for the development of co-generation plant which is absolutely very important in the electric power systems of the near future. The study involved in this project is to determine the optimal allocation and sizing of the DG in order to minimize the losses in the system. Fast Voltage Stability Index (FVSI) technique has been used with the objective to identify the suitable location for the distributed generation in the networks. FVSI is used as the measuring instrument in predicting the sensitive lines which will be used to identify the location for DG installation. Once the locations are determined, Particle Swarm Optimization (PSO) technique is developed to identify the optimal size of the DG. It is an algorithm that represents the behavior of a flock of birds or a school of fish.